Challenges of bacterial meningitis case management in low income settings: an experience from Ethiopia. Issue 7 (30th May 2016) - Gudina, Esayas Kebede; Tesfaye, Markos; Adane, Aynishet; Lemma, Kinfe; Shibiru, Tamiru; Pfister, Hans‐Walter; Klein, Matthias
Abstract: Objective: To investigate the current diagnostic and therapeutic strategies used in the care of patients with suspected bacterial meningitis at teaching hospitals in Ethiopia. Methods: This was a hospital‐based retrospective study conducted at four teaching hospitals in different regions of Ethiopia. Participants were patients aged 14 years and older treated for suspected bacterial meningitis. Presenting complaints, diagnostic strategies used and treatments given were obtained from clinical records. Result: A total of 425 patients were included in the study; 52.7% were men and 83.8% were younger than 50 years. Fever, headache, neck stiffness and impaired consciousness were the most common clinical presentations; 55.5% underwent lumbar puncture. Overall, only 96 (22.6%) patients had cerebrospinal fluid abnormalities compatible with bacterial meningitis. A causative bacterium was identified in only 14 cases. Ceftriaxone was used as the empiric treatment of choice, either alone or in combination with other antibiotics; 17.6% of patients were also given vancomycin. Adjunctive dexamethasone was given to 50.4%. Conclusion: Most patients treated as bacterial meningitis did not receive a proper diagnostic workup. The choice of antibiotic was not tailored to the specific clinical condition of the patient. Such an approach may result in poor treatment outcomes and lead to antibiotic resistance. Management of patients with suspected bacterial meningitis should be supported by analysis of cerebrospinal fluid, and treatment should be tailored to local evidence and current evidence‐based recommendations.